ANALISIS IMPLEMENTASI KEBIJAKAN RENCANA AKSI DAERAH (RAD) MDG’s POINT 5 DALAM UPAYA MENINGKATKAN KESEHATAN IBU DI KOTA SEMARANG - Fani Alizi Ilmifaluthi; Sutopo Patria Jati; Putri Asmita Wigati (Jurnal Kesehatan Masyarakat (Undip), 2015)
Implementation of a regional action plan is a document that refers to regional development for the increasing achievement of health development in the Region,the Regional Action Plan removes the MDG's. Semarang city includes as the category of the highest maternal mortality rate in fifth place in Central Java, so it is necessary to seek to reduce AKI, the government issued a regulation mayor No. 14 In 2013, a testament to the commitment of RAD MDG's to support the acceleration of the achievement of the MDG's in the improvement of maternal health in point 5. This study used a qualitative research design approach Retrospective study of population the local area that Health Departement, Bapermas and BAPPEDA.This study used purposive sampling thatwas taken from five respondents consisted of 2 main Informants and 3 Triangulation Informants. Analysis of the data presented in the discussion of the descriptive approach. Based on the results of in-depth interviews (depth interview) is that the implementation of the Regional Action Plan point 5 Maternal Health in document indicator RAD MDG's are used not in line with the indicators used by district Departement particular to maternal health, the lack of information with the involvement of stakeholders, barriers and challenges are not optimal integration between central and local government, which has not been structured system, and lack of funds. Then, from the aspect of good communication is not optimal communication both sectors and programs. Disposition aspects of the lack of support and commitment of the entire structural level are in accordance with official rules. Resource aspects of resource constraints, both infrastructure and funds as well as aspects of Bureaucratic Structure constrained schedule so that the intensity less intense coordination among stakeholders